Popularity Trap: Communication Ethic of Indonesia Public Figures on Instagram - Irma Purnama sari; Dede L Chaerowati (UIR Press, 2026)
Popularity is a double-edged sword for public figures, especially in today’s era of social media. Through social media platforms like Instagram, a public figure can easily increase their popularity through the content or posts they share. This study focuses on the case of an Indonesian public figure who was accused of defaming a police officer on social media. The incident caused a setback in their life. A public figure usually has a large number of followers on their social media, so any message they share will always attract attention and greatly affect many people. Therefore, when communicating in the virtual world, public figures must pay attention to digital communication ethics. This research uses a qualitative case study approach by collecting data through interviews and digital observation This research is significant because it reveals how digital popularity can become a trap that leads to the downfall of public figures in the era of viral culture. Theoretically, this study enriches the development of communication ethics theory and digital reputation. Practically, the findings are useful for increasing public awareness to be more responsible in the digital space. These findings provide input, especially for social media content creators, to be more careful and wise in delivering their information to the general public, because every action and word in the digital space has consequences or effect